2019
DOI: 10.21608/ejrsa.2019.10024.1066
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating Effect of Gamma Radiation on Some Active Compounds in Eggplant Fruits

Abstract: A FIELD experiment was performed to study the effect of gamma irradiation (0.0, 50 and 100Gy) on growth parameters and bioactive compounds of different parts of eggplant. All growth parameters studied showed an increase when using a dose of 50Gy gamma rays. Also, 50Gy increased total phenolic contents (2.140, 4.039 and 2.965mg/g DW) for pulp, peel and whole fruits, respectively. A dose level at 50Gy increased flavonoid contents (0.835, 4.301 and 3.166mg/g DW) for pulp, peel and whole fruits, respectively. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
(35 reference statements)
3
8
0
3
Order By: Relevance
“…In addition, the fact that the plants could not be obtained at a salt stress of 200 mM was another evidence of the sensitivity of 'F16'. Simple organic molecules, such as free amino acids, are involved in the regulation of plant osmosis in saline soil conditions (Aly et al, 2019b). Consistent with this study, studies in different plants show that amino acid synthesis is related to the plant's stage of development, intensity, and duration of the stress (Yang et al, 2015;Farhangi-Abriz and Ghassemi-Golezani, 2016;Xie et al, 2020).…”
Section: Discussionsupporting
confidence: 59%
“…In addition, the fact that the plants could not be obtained at a salt stress of 200 mM was another evidence of the sensitivity of 'F16'. Simple organic molecules, such as free amino acids, are involved in the regulation of plant osmosis in saline soil conditions (Aly et al, 2019b). Consistent with this study, studies in different plants show that amino acid synthesis is related to the plant's stage of development, intensity, and duration of the stress (Yang et al, 2015;Farhangi-Abriz and Ghassemi-Golezani, 2016;Xie et al, 2020).…”
Section: Discussionsupporting
confidence: 59%
“…Topuz & Ozdemir (2004) published as a consequence of gamma irradiation treatment, that phenols contents had been significantly enhanced in relation to tannin degradation and the modification of molecule structure. Furthermore, phenylalanine ammonia-lyase enzyme recreation, which is accountable for polyphenolic acid synthesis, was increased by increasing the gamma irradiation dose level (Aly, Eliwa, & AbdEl-Megid, 2019;Oufedjikh, Mostafa, Josèphe Amiot, & Lacroix, 2000). The contemporary findings have been reported by Harrison & Were (2007), who showed that the rise of date fruits phenolic content should be given to their launch from glycosidic precursors and the degradation of bigger polymeric phenolic compound to lower gadgets through gamma-ray treatments.…”
Section: Total Phenolic and Total Flavonoid Contentsmentioning
confidence: 85%
“…The elevated doses of radiation harm plants to a large extent (Hegazi & Hamideldin, 2010). In addition, there are some evidences from literature that the exposure of low ionizing radiation dose caused stimulation of growth (Aly, Eliwa, & Abd EL-Megid, 2019a;El-Beltagi, Mohamed, Mohammed, Zaki, & Mogazy, 2013).…”
Section: Resultsmentioning
confidence: 99%